2009
DOI: 10.1007/s11270-009-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Level Assessment on the Boukornine National Park (Tunisia) using Plant Biomonitoring: Influence of Altitudinal Parameter and Meteorological Conditions

Abstract: The variations of tropospheric ozone levels was assessed for the first time in the Boukornine National Park (N.E. Tunisia) by detection of leaf injury development on Nicotiana tabacum "Bel-W3" exposed to environmental conditions during summer 2004. Two cultivars of tobacco (Nicotiana tabacum), Bel-W3 (sensitive) and Bel-B (resistant to ozone), were used for this biomonitoring study. These cultivars were dispersed in 24 different biostations, according to a square grid mesh, every 2 weeks. Four successive cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Using meteorological data from the period of June 2004 to July 2004 from the national park of the Tunisian coast, it is found that O 3 concentration variation in summer is closely related to weather elements such as air temperature, rainfall, and wind over the coastal region. Their experimental study suggested that the local environment and meteorological conditions significantly influence temporal and spatial variations in O 3 distribution (Mechergui et al, 2009). Alghamdi et al investigated the effects of relevant meteorological variables on frequently high NO 2 and O 3 concentrations in the coastal cities of Saudi Arabia in 2012-2013. They discussed the influence of seasonal variations under meteorological conditions on the O 3 concentration and indicated that O 3 concentration values peak in the summer and drop in the winter (Andreas and Jochen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Using meteorological data from the period of June 2004 to July 2004 from the national park of the Tunisian coast, it is found that O 3 concentration variation in summer is closely related to weather elements such as air temperature, rainfall, and wind over the coastal region. Their experimental study suggested that the local environment and meteorological conditions significantly influence temporal and spatial variations in O 3 distribution (Mechergui et al, 2009). Alghamdi et al investigated the effects of relevant meteorological variables on frequently high NO 2 and O 3 concentrations in the coastal cities of Saudi Arabia in 2012-2013. They discussed the influence of seasonal variations under meteorological conditions on the O 3 concentration and indicated that O 3 concentration values peak in the summer and drop in the winter (Andreas and Jochen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Using meteorological data from the period of June 2004 to July 2004 from the national park of the Tunisian coast, it is found that O 3 concentration variation in summer is closely related to weather elements such as air temperature, rainfall, and wind over the coastal region. Their experimental study suggested that the local environment and meteorological conditions significantly influence temporal and spatial variations in O 3 distribution (Mechergui et al, 2009). Alghamdi et al investigated the effects of relevant meteorological variables on frequently high NO 2 and O 3 concentrations in the coastal cities of Saudi Arabia in 2012-2013.…”
Section: Introductionmentioning
confidence: 99%